EVALUATION OF EFFECTIVENESS OF VITAMIN TEACHER PORTAL - Kuscu, Meltem; Arslan, Hasan (European Scientific Journal, ESJ, 2015)
Distance education systems have been developing rapidly in the field of education. Since the beginning of FATIH (Opportunities to Increase and Technology to Improve Motion) Project applications, educational softwares and the concept of e-learning have been important concerns. Besides the lack or insufficiency of softwares for tablets or smart boards, the education content websites which already exist have been struggling to take part in this field. As a result, it is inevitable that there has been a competition between government supported applications and private sector. Vitamin Teacher Portal is an application that serves as a teacher training program. It is a distance education website designed for teachers to improve their both personal and professional skills. It includes live courses, forum, shares, teachers’ resources and educational videos. It is a synchronous application with Vitamin Education website which is designed for students.In this study, qualitative research method has been used. It is conducted with teachers who use Vitamin Teacher Portal to have valid results. The aim of this study is to work out the sufficiency level of this application from the point of view of teachers. By this means, it could be work out whether it is sufficient enough to meet the needs of teachers or not. We also to find out how effectively teachers, what they acquired from the portal in class.